2015
DOI: 10.3346/jkms.2015.30.11.1618
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Carcinoma Risk of Compensated Cirrhosis Patients with Elevated HBV DNA Levels according to Serum Aminotransferase Levels

Abstract: Sometimes, hepatitis B virus (HBV)-related cirrhotic patients with normal aminotransferase levels are closely followed-up for the elevation of aminotransferase levels instead of prompt antiviral therapy (AVT). We analyzed the long-term hepatocellular carcinoma (HCC) risk according to the aminotransferase levels in a retrospective cohort of 1,468 treatment-naïve, HBV-related, compensated cirrhosis patients with elevated HBV DNA levels (≥2,000 IU/mL). Based on aminotransferase levels, patients were categorized i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
0
12
0
2
Order By: Relevance
“…When assessed by specific treatment criteria, the 5‐year cumulative HCC incidence rate was generally high for patients with cirrhosis [15.1%, 13.9% and 8.2% for those with elevated HBV DNA levels (>2000 IU/mL), low‐level viremia (20‐2000 IU/mL) and undetectable HBV DNA (<20 IU/mL)]. This finding suggests that cirrhotic patients require special attention for their increased HCC risk . Specifically, cirrhotic patients with low‐level viremia were at increased risk.…”
Section: Discussionmentioning
confidence: 99%
“…When assessed by specific treatment criteria, the 5‐year cumulative HCC incidence rate was generally high for patients with cirrhosis [15.1%, 13.9% and 8.2% for those with elevated HBV DNA levels (>2000 IU/mL), low‐level viremia (20‐2000 IU/mL) and undetectable HBV DNA (<20 IU/mL)]. This finding suggests that cirrhotic patients require special attention for their increased HCC risk . Specifically, cirrhotic patients with low‐level viremia were at increased risk.…”
Section: Discussionmentioning
confidence: 99%
“…Decision to treat is based on an assessment of the risks and benefits of the treatment. Although there are still some concerns over long-term safety of NUCs, given the potential harms and potential benefits of AVT, and data from our study ( 1 ), prompt initiation of AVT seems reasonable approach for cirrhotic patients with elevated HBV DNA levels, even for those with normal ALT levels. Lastly, quantitative hepatitis B surface antigen levels are not measured for our cohort.…”
mentioning
confidence: 83%
“…We appreciate the valuable comment by Khosravi et al on our recently published article ( 1 ). First, Khosravi et al, suggested analyzing the impact of body mass index (BMI) on the risk of hepatocellular carcinoma (HCC).…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…We read with a great interest the article written by Lee and colleagues entitled "Hepatocellular Carcinoma Risk of Compensated Cirrhosis Patients with Elevated HBV DNA Levels according to Serum Aminotransferase Levels" which was recently published in your Journal of Korean Medical Science ( 1 ). The authors concluded the beneficial effects of prescribing appropriate anti-viral therapy (AVT) for reducing HCC risk in cirrhotic patients with elevated HBV DNA and normal aminotransferase levels.…”
mentioning
confidence: 99%